2011
DOI: 10.1089/jop.2010.0175
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxyethylene Hydrogenated Castor Oil Modulates Benzalkonium Chloride Toxicity: Comparison of Acute Corneal Barrier Dysfunction Induced by Travoprost Z and Travoprost

Abstract: Methods: Corneal transepithelial electrical resistance (TER) was measured in live white Japanese rabbits by two Ag/AgCl electrodes placed in the anterior aqueous chamber and on the cornea. We evaluated corneal TER changes after a 60-s exposure to travoprost Z, travoprost, and 0.015% BAC.Similarly, TER changes were evaluated after corneas were exposed for 60 s to the travoprost additives EDTA, boric acid, mannitol, trometamol, and polyoxyethylene hydrogenated castor oil 40 (HCO-40) with or without BAC. Corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(34 reference statements)
1
11
2
1
Order By: Relevance
“…Furthermore, it was reported that the corneal epithelium of the 0.02% BAC-treated cornea showed detaching and wrinkling of the superficial cells, dissociations between the cells, and degenerated microvilli. 44 In conclusion, the results of the present study indicate that the corneal TER after applying antiglaucomatous eyedrops tended to decrease concomitantly with increasing the concentration of the BAC included as a preservative. Moreover, the pretreatment with Hyalein Mini reduced the extent of decrease in the corneal TER observed after application of each antiglaucomatous eyedrop alone.…”
supporting
confidence: 54%
“…Furthermore, it was reported that the corneal epithelium of the 0.02% BAC-treated cornea showed detaching and wrinkling of the superficial cells, dissociations between the cells, and degenerated microvilli. 44 In conclusion, the results of the present study indicate that the corneal TER after applying antiglaucomatous eyedrops tended to decrease concomitantly with increasing the concentration of the BAC included as a preservative. Moreover, the pretreatment with Hyalein Mini reduced the extent of decrease in the corneal TER observed after application of each antiglaucomatous eyedrop alone.…”
supporting
confidence: 54%
“…Some suggest travoprost with sofZia® is safest for the cornea;2022 however, we could not directly compare it with travoprost preserved with BAC in NTG patients because the latter is not available in Japan. The result in this study suggests that travoprost with sofZia® is safe on the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Further, BAC has also been shown to induce precorneal tear film instability on the corneal surface and the appearance of dry spots. 16 Overall, these findings suggest that when evaluating drug toxicity, it is necessary to also consider potential interactions that could occur with the additives commonly found with BAC. 12,13 Therefore, the chronic use of eye drops containing BAC can potentially have an adverse effect on the cornea.…”
mentioning
confidence: 99%